PENGARUH PERSEPSI PROFESI, KESADARAN ETIS, DAN INDEPENDENSI AUDITOR TERHADAP KOMITMEN PROFESI AKUNTAN PUBLIK (Survei pada Auditor di Kantor Akuntan Publik di Surakarta dan Yogyakarta) - Anik Susilowati, Rispantyo & Djoko Kristianto (Universitas Slamet Riyadi, 2017)
Auditors in their profession are required to have a good profession'scommitment to clients, the public and fellow accountant. The purpose of this studywas to analyze the influence of the perception of the profession, ethical awarenessand commitment to the independence of auditors of public accounting profession.This study uses survey method, the type of data used quantitative and qualitativedata, the data source used primary data and secondary data. The population in thisstudy are all auditors who work in public accounting firms in the region of Surakartaand Yogyakarta. The number of samples in the study based on the number ofquestionnaires returned, as many as 41 respondents. The sampling technique usingpurposive sampling. Data collection methods are used: questionnaires anddocumentation. Data analysis technique used to test the validity, reliability test,classic assumption test, multiple linear regression analysis, t-test, f-test, and thecoefficient of determination. In conclusion that: 1) The influence of the profession'sperception of the public accounting profession's commitment is positive notsignificant. 2) The influence of ethical awareness of the public accountingprofession's commitment is positive and significant. 3) Influence of independence ofthe auditor on the commitment of the public accounting profession is negative andsignificant. 4) The perception of the profession, ethical awareness and auditorindependence simultaneously significant effect on the dependent variable is thecommitment of the public accounting profession in the public accounting firm ofSurakarta and Yogyakarta.Keywords: Perception profession, ethical awareness, auditor independence, andcommitment to the profession